Chain flexibility and glass transition temperatures of poly(n-alkyl (meth)acrylate)s: Implications of tacticity and chain dynamics. (20th January 2021) - Li, Tianyu; Li, Hui; Wang, Huiqun; Lu, Wei; Osa, Masashi; Wang, Yangyang; Mays, Jimmy; Hong, Kunlun
Abstract: The relationship between chain microstructure and glass transition temperature (Tg ) is complicated for poly(alkyl methacrylate)s and poly(alkyl acrylate)s. Despite intensive studies, relationships between the structures of these polymers and their properties, including solution characteristics and Tg, are still controversial. Solution properties, chain conformations, including Flory's characteristic ratio (C∞ ), persistence length (lp ), and chain diameters, and Tg are reported for series of poly(n-alkyl acrylate)s and poly(n-alkyl methacrylate)s having alkyl side chain lengths (n) ranging from 1 to 10 carbons in length, with uniform and well-characterized tacticities. Chain flexibilities of both series of polymers decrease as n increases, reflecting increased hindrances to rotation about backbone bonds as side chains become longer. Conversely, the Tg s for both series of polymers decrease substantially as n increases, reflecting the greater side chain mobilities of long alkyl substituents. For shorter alkyl chain lengths, Tg s for the poly(n-alkyl acrylate)s are much lower than for the corresponding poly(n-alkyl methacrylate)s, a difference which has been attributed in the past to the presumed reduced chain flexibility of polymethacrylates due to the presence of the α-methyl substituent. However, contrary to such expectations, C∞ and lp values for these two series of polymers are nearly identical at a given n value, except for the longest n-alkyl substituents. Instead, the differences in Tg may be attributed to the differences in tacticity of the two series – almost ideally atactic for the poly(n-alkyl acrylate)s but high in syndiotacticity for the poly(n-alkyl methacrylate)s. The Tg s for the two series of polymers approach that of polyethylene at longer alkyl chain lengths. In addition, the effects of tacticity and chain dynamics on C∞, lp, and Tg of poly(methyl methacrylate) is discussed. Graphical abstract: Image 1 Highlights: Effect of side chain length on chain flexibility and glass transition temperature of poly(n-alkyl (meth)acrylate)s. Influence of tacticity on chain flexibility and glass transition temperature of poly(n-alkyl (meth)acrylate)s. Flory's characteristic ratio was correlated to the isotactic content of poly(methyl methacrylate). Touched-bead wormlike chain model was used to analyze the conformations of poly(n-alkyl (meth)acrylate)s.